Blowing the whistle : barriers to federal employees making disclosures : a report to the President and the Congress of the United States (United States Government Printing Office, 2017)
This report compares data from Merit Principles Surveys conducted in 1992 and 2010 to describe the extent to which perceptions of retaliation against Federal employees who report wrongdoing remains a serious problem. The results indicate that if an agency creates a culture where its employees believe that management wants to be told about wrongdoing and will address issues raised by employees, then employees are more likely to notify management when they see a problem. The report also explains why agencies should do more to ensure that employees receive quality training about how they can disclose wrongdoing and how they can exercise their rights if they perceive that they have experienced retaliation for whistleblowing activities.